P312 Combination corticosteroids with, 5-aminosalicylic acid versus corticosteroids alone in the treatment of hospitalized patients with acute severe ulcerative colitis: A multi-center randomized controlled trial. (21st January 2022) - Ben-Horin, S; Har-Noy, O; Katsanos, K H; Xavier, R; Chen, M H; Gao, X; Schwartz, D; Cheon, J H; Cesarini, M; Bojic, D; Protic, M; Theodoropoulou, A; et al.
Abstract: Background: Corticosteroids are the mainstay of treatment for hospitalized patients with acute severe ulcerative colitis (ASUC). However, whether the addition/continuation of, 5-aminosalicylates (5ASA) with corticosteroids during hospitalization is superior to corticosteroids alone is unknown Methods: This was a randomized controlled investigator-blinded clinical trial conducted in ten centers in six countries. Patients hospitalized with ASUC (Lichtiger score ≥10) were eligible. Patients received corticosteroids alone or corticosteroid+5ASA (4gr/day mesalamine) by a stratified randomization according to, 5ASA use prior to admission. The primary outcome was the percentage of patients who responded to treatment by day, 7, defined by a drop>3 points in the Lichtiger score and an absolute score<10 without the need for rescue medications or colectomy. Results: 346 patients were screened and, 149 were included (70/149 females, median age, 41). Of these, 73 received corticosteriods+5ASA and, 76 corticosteroids alone. For the primary outcome, 53/73 (72.6%) of patients receiving corticosteroids with, 5ASA responded versus, 58/76 (76.3%) of patients on corticosteroids alone (OR, 0.82, 95%CI, 0.39–1.72, p=0.60). There was no difference between groups in duration of hospitalization or CRP normalization rate. Colectomy rate up to day, 90 was similar, but in an exploratory analysis the need for biologics among patients receiving combination corticosteroids with, 5ASA was numerically lower by day, 30 (p=0.11) and day, 90 (p=0.07). Conclusion: In this prospective randomized controlled trial, combination, 5ASA with corticosteroids during hospitalization did not benefit patients admitted with ASUC more than corticosteroids alone. An exploratory finding of a reduced need for biologics at, 90 days in the combination group merits further evaluation. ClinicalTrials.gov ID: NCT01941589